The socio economic factors in Rustenburg that fuel sexually transmitted diseases (STDs) and which could result in the transmission of the human immunodeficiency virus (HIV) - Ntumba, Kalala (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.